THE ANALYS OF INFLUENCE OF EXTRANEOUS SMELLS ON A FUNCTIONAL CONDITION OF BIOOBJECT - Ekaterina Dudkina (Biomedicinskaâ Inženeriâ i Èlektronika, 2018)
The work is devoted working out regression’s model of influence of massage on weakening and regenerative response of an organism. The given model is constructed on the basis of experimental data on monitoring of the cores and derivative indicators of heart-vascular and nervous systems directly after carrying out of manual or hardware massage.  The comparative analysis between influence on an organism manual and hardware massage is carried out. It is established, that manual massage operates locally and renders more necessary effect rather than hardware which can be used in definite purposes. The constructed model considers parameters of a masseur which local an effect can have on a site of a massed skin.